The relationship between anesthesia, surgery and postoperative immune function in cancer patients: a review - Guo, Rui; Yang, Wen-wen; Zhong, Mao-lin; Rao, Pan-guo; Luo, Xin; Liao, Bao-zhen; Lei, Xing-heng; Ye, Jun-ming (Frontiers in Immunology, 2024)
This review comprehensively examines the impact of anesthesia and surgical interventions on the immune function of cancer patients postoperatively. Recent studies have shown that surgery and its accompanying anesthesia management can significantly influence immune function in cancer patients, potentially affecting their prognosis. This review synthesizes clinical studies and basic research to summarize the specific effects of anesthesia methods, drugs, postoperative analgesia, intraoperative transfusion, surgical techniques, and trauma extent on the immune function of cancer patients post-surgery. Additionally, this review discusses optimization strategies based on current research, aiming to refine anesthesia and surgical management to maximize the preservation and enhancement of postoperative immune function in cancer patients, with the potential to improve clinical outcomes.